LENGTH OF PATERNAL EDUCATION IS ASSOCIATED WITH HEIGHT-FOR-AGE OF SCHOOL CHILDREN IN RURAL AREA OF SEPATAN TIMUR-TANGERANG - Angkasa, Dudung; Sitoayu, Laras; Jus'at, Idrus (GIZI INDONESIA, 2018)
Paternal educational status plays an important role in long-term nutritional status of children. The objective of this study was to investigate the association between paternal factors and school children nutritional status in rural setting, Indonesia. A cross-sectional study carried out in September  up to November 2015 involving 368 primary public school children in Sepatan Timur, Tangerang. Structured questionnaires were administered to parents, containing household characteristics such as length of school year, working status, number of siblings. Children weight and height were measured using a weighing scale and microtoise, respectively. Anthropometric indices, height-for-age (HAZ) and body mass index for-age (BAZ), were produced by using WHO-Antroplus. Children’s food intake and snacking habits were assessed using single 24 hours food recall and food frequency questionnaire, respectively. Others variables were physical activity and infectious disease history. Multiple regression analyses were employed to enquire research questions. Results indicated that children with father’s educational status less than 9 years had a significant 0.607 lower HAZ if compared to those educational status more or equal to 9 years after adjustment for mother’s schooling year, working status, number of household member, children’s history of diarrhea and physical activity status, sex, age and snacking frequency. Conclusion, father’s educational status was associated with height for age among school children in rural area of Sepatan Timur. ABSTRAK Pendidikan orang tua berperan penting dalam menentukan status gizi anak dalam jangka panjang. Penelitian bertujuan menganalisis hubungan faktor orang tua dengan status gizi anak sekolah di wilayah pedesaan. Penelitian menggunakan desain potong lintang dilaksanakan selama September-November 2015 dengan melibatkan 368 anak sekolah dasar negeri di Sepatan Timur, Tangerang. Kuesioner terstruktur diberikan pada orang tua untuk mengetahui lama sekolah, status pekerjaan, dan jumlah anak. Berat dan tinggi badan akan diukur dengan timbangan badan dan microtoise kemudian dihitung indeks antropometri tinggi badan menurut umur (TB/U) dan indeks massa tubuh menurut umur (IMT/U). Konsumsi sampel dinilai dengan food recall 24 jam satu hari dan kuesioner frekuensi makanan. Variabel lain yang diamati ialah aktivitas fisik dan riwayat infeksi. Analisis Regresi berganda digunakan untuk menjawab tujuan. Hasil menunjukkan bahwa sampel dari ayah yang berpendidikan <9 tahun lebih rendah skor TB/U sebesar 0,607 poin dibandingkan sampel dari ayah yang berpendidikan >9 tahun setelah dikontrol lama pendidikan ibu, status pekerjaan, jumlah anak, riwayat diare, aktivitas fisik, jenis kelamin, umur dan frekuensi jajan anak. Penelitian ini menyimpulkan bahwa pendidikan ayah yang rendah berhubungan dengan tinggi badan anak pada anak sekolah di wilayah pedesaan, Sepatan Timur. Kata kunci: pendidikan ayah, status gizi, anak sekolah, pedesaan